Learning Innovation with Nature-Based Learning Model at Jogja Green School Elementary School - Rini, Cahya Ramadhani Setya; Rahmawati, Selly (Universitas Pendidikan Indonesia, 2025)
This study aims to determine the method of Learning Together with Nature (BBA) at SD Jogja Green School from planning, implementation, evaluation, as well as supporting and inhibiting factors. The method used is descriptive qualitative with data collected through observation, interviews, and documentation from the school coordinator/principal, teachers, students, and parents. Data analysis was done by data collection, data reduction, data presentation, and conclusion, and data validity was checked through triangulation of sources and techniques. The results showed that the BBA method at SD Jogja Green School involves several processes, such as planning in accordance with indicators, implementation with nature concept constructive play learning activities, evaluation with assessment principles and with observation and portfolio methods. Supporting and inhibiting factors for the implementation of BBA in this school include teachers, parents, peers, and infrastructure.